Effects of Argument Quality, Need for Cognition and Issue Involvement to The Attitude Toward a Message Given Through Persuasive Communication - Sri Hartati (Jurnal Psikologi, 2005)
The present study was an experimental study. The goal of the study was to  find out the effects of the quality of an argument, need for cognition  (NC)  and  the  degree  of  issue involvement, altogether  in determining  the attitude  toward  a message  given  through persuasive communication. The subjects were 80 students from 121 fresh  (entry)  students  of  the  Faculty  of Psychology, Gadjah Mada University, year 1995/1996. The subject was then  randomly assigned to four manipulation groups. Each group was  given  one  of  the  four  types  of manipulation, which were combinations of the quality of the arguments (strong or weak) and the degree of issue involvement (high or low). After the manipulation, the subjects were given an attitude scale measuring their  favorableness toward the issue. The data was analyzed with three ways factorial ANOVA. The results supported the hypothesis of the study. It can be concluded that when argument was strong, the higher motivation (that is, the higher NC and the  involvement) to process the message, the stronger the favorableness toward the  issue. On the other hand, when the argument was weak, higher motivation resulted in weaker favorableness. This study also found that the NC as a motivating  factor had stronger  influence rather than issue  involvement. Keywords:  argument  quality,  need  for cognition,  issue involvement